2017
DOI: 10.1002/etep.2364
|View full text |Cite
|
Sign up to set email alerts
|

Optimal scheduling of the plug-in electric vehicles aggregator energy and regulation services based on grid to vehicle

Abstract: Summary The advantage of grid‐to‐vehicle power over vehicle to grid is that the existing power grid infrastructure and technology are able to support its operation. In this paper, a regulation operation framework for grid‐to‐vehicle–based plug‐in electric vehicle (PEV) aggregator is proposed. Based on that, PEVs can provide regulation services during charging. The objective function consider the influence of regulation services on the energy of battery charging for PEVs and the constraint of systems for batter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 80 publications
(35 citation statements)
references
References 24 publications
0
23
0
Order By: Relevance
“…The program restrictions are given by Equation (7). SoC t l , in %, is the EV l level; this parameter must not exceed the minimum and maximum limits, SoC min and SoC max , respectively.…”
Section: Coordinated Ev Charging and Discharging Controlmentioning
confidence: 99%
See 2 more Smart Citations
“…The program restrictions are given by Equation (7). SoC t l , in %, is the EV l level; this parameter must not exceed the minimum and maximum limits, SoC min and SoC max , respectively.…”
Section: Coordinated Ev Charging and Discharging Controlmentioning
confidence: 99%
“…Thus, coordinated battery charging can alleviate some of the negative effects caused by the uncoordinated charging such as system overload and voltage limit violation . Moreover, battery charging coordination using price signals is able to assist in the management of energy by stimulating EV charging during periods of low electricity demand …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In off‐board charging, particularly in commercial installations (Level 3 charging), EV batteries are charged with the power quality indices meeting the relevant standards, using modified unified power quality conditioner . The plug‐in hybrid electrical vehicle batteries are employed in Aly et al and Hou et al to mitigate the voltage fluctuations of the network fed by solar power, using a coordinated control strategy and regulation‐based algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Taking above‐mentioned concerns into consideration, the system studies have been carried out at different levels of penetration of electric vehicles. () It is found that the peak load demand increases, and further, it is suggested that controlled charging strategies can be employed to reduce the losses, invested, and operating cost. The effect of electric vehicle on voltage profile under different situation is also studied in the literature.…”
Section: Introductionmentioning
confidence: 99%